THE EMOTIONAL INTELLIGENCE OF STUDENTS WHO ARE SITTING A SPECIAL-ABILITY EXAMINATION - Coban, Bilal; Karademir, Tamer; Acak, Mahmut; Devecioglu, Sebahattin (Soc Personality Res Inc, 2010)
We aimed to detect the differences in emotional intelligence in young people according to some sociodemographic variables. A total of 170 people who were sitting a special-ability examination in order to gain a place in the physical education and sports teaching department at a university formed the sample. We found that there were statistically significant differences in emotional intelligence levels according to the variables of age, hometown, participation in social and sports activities, self-description, and description of family, as well as in the behaviors of the families towards the adolescent. There were no significant differences according to gender, alma mater, or the income level of the family.
Keywords: emotional intelligence; sport; family attitude; adolescence; sports